Omejitve ustanavljanja gospodarskih družb, identifikacija delničarjev in uresničevanje pravic na skupščini - Prelič, Saša (Podjetje in delo, 2021)
The article examines the rights of companies to identify their respective shareholders, to transmit of information and facilitate exercising of shareholders' rights, according to the implementation of Directive (EU) 2017/838 of the European Parliament and of the Council of 17 May 2017 amending Directive 2007/36/EC as regards of encouragement of long-term shareholder engagement. The directive was implemented with Law amending Law on commercial companies (ZGD-1K).
Keywords: chain of intermediaries; Delničarska direktiva II; identification of shareholders; identifikacija delničarjev; intermediary; javne delniške družbe; legal restrictions; listed public limited company; novela ZGD-1K; omejitve ustanavljanja gospodarskih subjektov; posrednik; posredniki v verigi; posredovanje informacij; restrictions of establishment of companies; Shareholder Rights Directive II; transmission of information